Collaborative management: a sustainable natural tourism development model - Fitria Earlike Anwar Sani; Mochammad Musafa'ul Anam (Universitas Merdeka Malang, 2022)
In the development of natural tourism areas in the Sirah Kencong Tourism Area, the regional government of Blitar Regency, East Java Province has made various efforts and efforts. However, this effort still has some obstacles in its implementation. This study aims to develop a sustainable nature tourism development model based on collaborative management. This study uses qualitative methods supported by quantitative data through Interpretive Structural Modeling (ISM) analysis. Data was collected through interviews, Focus Group Discussions, and literature studies such as RIPDA and the Master Plan for the Sirah Kencong area. The ISM (expert survey) questionnaire as a research instrument was used to obtain information about the contextual relationship of each element in the Interpretive Structural Modeling (ISM) analysis involving 10 experts. The results of this study indicate that the development of natural tourism areas requires a more structured model with four strategies, namely (i) the establishment of collaborative management, (ii) increasing tourist attraction and tourism activities, (iii) integrating destination governance, and (iv) Increasing tourism products. In more succinct terms, the establishment of collaborative management between the regional government, academia, the private sector, the community, and the mass media is a solution to the development of natural tourism areas in the tourist area of Blitar Regency.